1991
DOI: 10.1148/radiology.181.3.1947082
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid gland: US screening in a random adult population.

Abstract: High-frequency ultrasound examination of the thyroid was performed in 253 subjects (130 women and 123 men; age range, 19-50 years) that were randomly selected from the population in an area of Finland where goiter is not endemic. Thyroid echo abnormalities were detected in 69 subjects (27.3%). Prevalence of abnormalities increased with age, and women showed more lesions than did men in each of the 3 decades. The abnormality was solitary in 39 subjects (57%), multiple in 15 (22%), and diffuse in 15 (22%). Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
228
1
27

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(264 citation statements)
references
References 0 publications
8
228
1
27
Order By: Relevance
“…In a study including 635 volunteers who presented for a preventive health checkup, thyroid nodules were found by ultrasonography in 68% (1). In another study of 253 volunteers selected from a random sample of the population in Finland, thyroid nodules were found by ultrasound in 21% (2). Moreover, the prevalence of thyroid nodules in autopsy studies of patients without known thyroid disease varies between 30% and 50% (3).…”
Section: Introductionmentioning
confidence: 99%
“…In a study including 635 volunteers who presented for a preventive health checkup, thyroid nodules were found by ultrasonography in 68% (1). In another study of 253 volunteers selected from a random sample of the population in Finland, thyroid nodules were found by ultrasound in 21% (2). Moreover, the prevalence of thyroid nodules in autopsy studies of patients without known thyroid disease varies between 30% and 50% (3).…”
Section: Introductionmentioning
confidence: 99%
“…The number of thyroid incidentalomas is increasing due to widely use of highly sensitive ultrasonography for routine health examinations [4]. Previous studies have reported that incidental thyroid nodules are commonly detected at a rate of 30-50% on sonography [5,6] with a malignancy rate of about 7-15% [7][8][9][10]. Fine needle aspiration cytology (FNAC) is now established as a reliable and safe method to distinguish between benign and malignant thyroid nodules [8,11,12].…”
mentioning
confidence: 99%
“…detected, intensifying the need for better prognostic information. [3][4][5][6][7][8] A number of investigators have identified prognostic factors for …”
mentioning
confidence: 99%